2023
DOI: 10.1111/jcpe.13823
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and treatment of peri‐implant diseases—The EFP S3 level clinical practice guideline

Abstract: Background The recently published Clinical Practice Guidelines (CPGs) for the treatment of stages I–IV periodontitis provided evidence‐based recommendations for treating periodontitis patients, defined according to the 2018 classification. Peri‐implant diseases were also re‐defined in the 2018 classification. It is well established that both peri‐implant mucositis and peri‐implantitis are highly prevalent. In addition, peri‐implantitis is particularly challenging to manage and is accompanied by significant mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
88
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 150 publications
(91 citation statements)
references
References 144 publications
(404 reference statements)
3
88
0
Order By: Relevance
“…In this context, our choice of a 60-s instrumentation was based on clinical/ practical considerations. It should also be noted that AP during surgery is currently not recommended (Herrera et al, 2023). In one of the few clinical evaluations on the topic, Hentenaar et al (2022) failed to identify any clinically relevant benefits of AP in the surgical treatment of peri-implantitis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this context, our choice of a 60-s instrumentation was based on clinical/ practical considerations. It should also be noted that AP during surgery is currently not recommended (Herrera et al, 2023). In one of the few clinical evaluations on the topic, Hentenaar et al (2022) failed to identify any clinically relevant benefits of AP in the surgical treatment of peri-implantitis.…”
Section: Discussionmentioning
confidence: 99%
“…The consensus report also stated that the purpose of a surgical approach in the management of peri-implantitis is to provide access to the implant to facilitate surface decontamination. Although a standard surgical procedure was suggested to include cleaning/ decontamination of the implant surface using, for example, small pieces of gauze soaked in saline and removal of mineralized deposits with curettes, additional implant surface decontamination procedures were suggested to include mechanical/physical methods and/or chemical agents (Herrera et al, 2023). Results from systematic reviews performed in conjunction with the EWOP indicated that only few controlled studies exist on additional implant surface decontamination methods (Ramanauskaite et al, 2023;Wilensky et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For dental implants, a prosthetically guided position is considered important for long-term implant health (Herrera et al, 2023).…”
Section: Introductionmentioning
confidence: 99%